COVID-19: Impact on undergraduate nursing education in Sri Lanka - Ilankoon Mudiyanselage Prasanthi Sumudrika Ilankoon; Kisokanth Gnanaselvam; Sudath Shirely Pathmasiri Warnakulasuriya (SAGE Publishing, 2020)
"Novel Corona Virus" (COVID-19) is a new infectious disease spreading all around the world which has a significant morbidity and mortality globally at present. Nurses as frontline care provider in hospitals and community are exposed to a major risk. This brief report aims at providing an overview of COVID-19 impacts on Sri Lanka and to highlight educational implications from the perspective of nursing degree programs. The major impacts of COVID-19 on nursing education were unequal access to online distance learning, disruption of academic calendars, cancellation of clinical placements, teaching and learning gap, lack of facilities for online learning, disruption towards professional development, and inability to conduct proper clinical assessments and standard operationalization procedures. It suggests that higher education institutions should take actions to provide material support for students from low-income households to close the gap between teaching and learning and training for academics on different online teaching strategies.